Niezwykłe losy pierwszego drukowanego przekładu Koranu na język polski - Łapicz, Czesław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The first translation of the Quran, printed and published in 1858, was signed by Jan Musza Tarak Buczacki, a Tatar and Muslim from Podlasie in Poland. Today, however, is is known that the actual translators were two Philomats from Wilno, the priest Dionizy Chlewiński and Ignacy Domeyko. They performed the task in the 1820s for the Muslim Tatars of the Grand Duchy of Lithuania, who over generations had lost their knowledge not only of liturgic language (Arab), but also of their ethnic languages and dialects (Turkic). In this way, Lithuanian-Polish Muslims cut themselves off from the roots and sources of Islam. However, the attempts made by the translators to gain acceptance of Russian censors to publish the Polish rendition of the holy book of Islam were not successful. Only in the 1850s the acceptance was granted, after efforts made by Jan Murza Tarak Buczacki, whose name was put on the title page posthumously by the publisher. At the end of the 19th century an anonymous author, probably a Tatar and Muslim, converted the printed translation, authored by Buczacki, into a traditionalhand-written Tatar tefsir: the Polish version was overwritten by hand in the interlines, and synchronized with the Arab lines of the original Quran in Arabic. For dogmatic and religious reason, he transliterated the text form Latin alphabet into Arabic one, without changing the content of the translation. The manuscript is now kept in Museum of History of Religion in Grodno. This is the conclusion of the complicated history of the first Polish translation of the Holy Book of Islam.